The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10552-009-9431-y
|View full text |Cite
|
Sign up to set email alerts
|

Race, healthcare access and physician trust among prostate cancer patients

Abstract: Objective To study the effect of healthcare access and other characteristics on physician trust among black and white prostate cancer patients. Methods A three-timepoint follow-up telephone survey after cancer diagnosis was conducted. This study analyzed data on 474 patients and their 1,320 interviews over three time periods. Results Among other subpopulations, black patients who delayed seeking care had physician trust levels that were far lower than that of both Caucasians as well as that of the black pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Specifically, given that patients with indolent prostate cancer are unlikely to die of the disease, those who are treated aggressively may unnecessarily experience the morbidities associated with surgery or radiation, 23 with little to no benefit from treatment. [7][8][9] Men of high socioeconomic status and Caucasian men with prostate cancer have greater access to healthcare and health insurance coverage compared with men of low socioeconomic status and minority men, 24,25 which may be the underlying driver of high rates of aggressive therapy for their indolent prostate cancer. Our results demonstrated that men of high socioeconomic status, Caucasian men, and married men were only slightly more likely to be insured compared with men of low socioeconomic status, non-Caucasian men, and unmarried men, respectively, indicating that differences in rates of insurance coverage probably were not a major contributor to the sociodemographic differences in receipt of aggressive therapy observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, given that patients with indolent prostate cancer are unlikely to die of the disease, those who are treated aggressively may unnecessarily experience the morbidities associated with surgery or radiation, 23 with little to no benefit from treatment. [7][8][9] Men of high socioeconomic status and Caucasian men with prostate cancer have greater access to healthcare and health insurance coverage compared with men of low socioeconomic status and minority men, 24,25 which may be the underlying driver of high rates of aggressive therapy for their indolent prostate cancer. Our results demonstrated that men of high socioeconomic status, Caucasian men, and married men were only slightly more likely to be insured compared with men of low socioeconomic status, non-Caucasian men, and unmarried men, respectively, indicating that differences in rates of insurance coverage probably were not a major contributor to the sociodemographic differences in receipt of aggressive therapy observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The same treatment pattern is well characterized in AA men (27, 41, 42). In AAs, etiologies for treatment differences are multifactorial and include patient mistrust of physicians (43), general negative attitudes against surgery(44), and lack of access to care(26, 4548). Potential provider factors may include bias from known poorer outcomes in national data sets (26, 4653) and more challenging pelvic anatomy in AAs (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is some evidence from laboratory studies linking neurotransmitters associated with chronic stress to prostate cancer [29][30][31][32][33][34]. Additionally, some studies have found that lack of trust in physicians is associated with decreased PCa screening and delay in seeking PCa care, which may influence prostate cancer mortality [35,36].…”
Section: Discussionmentioning
confidence: 99%